A polymer, paper reinforcing agent and method for making the same

CN120399144BActive Publication Date: 2026-10-23YINGDELIANGSHI IND MATERIALS
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510607122.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-05-13
Publication Date
2026-10-23
Estimated Expiration
2045-05-13

AI Technical Summary

Technical Problem

[0003]专利技术中CN 116964147 A及CN 113785029 A描述了一种水性醛化物作为纸张增强剂,其为乙二醛改性阳离子聚丙烯酰胺类增强剂,其但是增强幅度不够,特别是用在短纤较多的体系中,其所得成品纸张强度增幅较少,从而限制了此类增强剂的广泛使用

Benefits of technology

[0025](1)本发明提供的增强剂为分子量适中、分散系数更小、网络密度更高、分子链更刚的一种组合物。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GHA0000015194650000121
    Figure GHA0000015194650000121
  • Figure GHA0000015194650000131
    Figure GHA0000015194650000131
  • Figure GHA0000015194650000141
    Figure GHA0000015194650000141
Patent Text Reader

Abstract

The application belongs to the field of high polymer, and discloses a polymer used for paper strength agent, which contains acrylamide structural unit, cationic structural unit containing cationic group, and functional structural unit used for improving polymer rigidity or crosslinking density; the weight average molecular weight of the polymer is 5-100 million, and the dispersion coefficient is less than 3. After the polymer is applied to the paper strength agent, the strength of the paper can be improved, and the water filtering performance can be improved. Meanwhile, the application also provides a preparation method of the polymer, a paper strength agent and a preparation method thereof.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymers, and more particularly to a polymer, a paper reinforcing agent, and a method for preparing the same. Background Technology

[0002] In the papermaking process, strength additives are often added to impart dry strength to the finished paper. Currently used dry strength additives include natural polymers such as modified starch and chitosan, as well as synthetic polymers such as acrylamide (PAM) and polyvinyl alcohol (PVA). Based on their charge properties, they can be classified into cationic (CPAM), anionic (APAM), and amphoteric dry strength additives (ACPAM).

[0003] The patented technologies CN 116964147 A and CN 113785029 A describe an aqueous aldehyde as a paper reinforcing agent, which is a glyoxal-modified cationic polyacrylamide reinforcing agent. However, the reinforcing effect is insufficient, especially when used in systems with a large amount of short fibers. The resulting finished paper shows only a small increase in strength, thus limiting the widespread use of this type of reinforcing agent.

[0004] The problem this solution aims to solve is: how to increase the reinforcing effect of paper strengthening agents on paper. Summary of the Invention

[0005] The purpose of this invention is to provide a polymer that, when applied to a paper strengthening agent, can improve the strength of the paper and simultaneously enhance its water filtration performance.

[0006] In addition, the present invention also provides a method for preparing the polymer, as well as a paper reinforcing agent and a method for preparing the same.

[0007] To achieve the above objectives, this application discloses a polymer for use as a paper reinforcing agent, wherein the polymer contains acrylamide structural units, cationic structural units containing cationic groups, and functional structural units for improving the rigidity or crosslinking density of the polymer.

[0008] The polymer has a weight-average molecular weight of 5 to 1,000,000 and a dispersion factor of 1.5 to 3.

[0009] Paper fiber strength is generally determined by four factors: 1. the strength of a single fiber; 2. the bond strength between fibers; 3. the bond area between fibers; and 4. the uniformity of the finished paper. Reinforcing agents are generally used to increase the bond area and strength of fibers, making more fibers denser and thus improving the overall bond strength, thereby increasing the overall strength.

[0010] To achieve affinity for fibers, especially short fibers, the polymer network utilizes hydrogen bonds, chemical bonds, and physical entanglement with the fibers to enhance fiber bonding and strength. Simultaneously, the polymer's molecular weight and dispersibility are also factors affecting its bonding stability with fibers. If the molecular weight is too small, although it can bond with fibers more quickly, the resulting strength is insufficient due to its low strength. Conversely, if the molecular weight is too large, the bonding speed is slower, resulting in poor paper uniformity and also limiting strength. Therefore, a suitable molecular weight is emphasized in this invention.

[0011] The molecular weight dispersibility of polymers, expressed as molecular weight statistics, can lead to insufficient strength performance if the dispersibility is too high. Therefore, obtaining polymers with low dispersibility coefficients is one of the objectives of this invention. Further optimization to achieve ideal strength, with a polymeric network structure capable of reacting with fibers, is key to realizing this objective.

[0012] Generally, polymers possess a certain network structure that allows for the retention of small fibers, enabling better fiber contact and stacking, thereby increasing strength. Secondly, paper strength is improved by enhancing the interaction strength between the polymer and the fibers. Finally, the overall strength of the paper is contributed by increasing the strength of the polymer itself.

[0013] In summary, this invention enhances the strength of the polymer by employing functional structural units, thereby improving the retention and fixation of small fibers and increasing paper strength. Simultaneously, by optimizing the molecular weight and molecular weight distribution, it further improves the retention and fixation of small fibers and maintains an appropriate rate of fiber bonding. Through these optimizations, a significant improvement in paper strength is achieved.

[0014] In the above-mentioned polymers, the weight-average molecular weight is 140,000 to 280,000 and the dispersion index is 2.3 to 2.8. Particularly preferred is that the weight-average molecular weight is 142,000 to 262,000.

[0015] The cationic monomer generally refers to a compound containing ammonium salts or other compounds containing tertiary amines, which ionizes into corresponding N+ ions in aqueous solution; more specifically, the acrylamide structural unit is acrylamide or methacrylamide; the cationic structural unit is one or more combinations of dimethyldiallylammonium chloride, methacryloyloxyethyltrimethylammonium chloride, acryloyloxyethyltrimethylammonium chloride, and tetraallylammonium chloride.

[0016] The aforementioned functional structural units refer to chemical substances that can give polymers specific morphological structures, especially monomers that can improve the rigidity of polymers or increase the density of more network structures in polymers.

[0017] The monomers that can improve polymer rigidity refer to those that make the polymer more rigid, which can generally be characterized by the polymer's glass transition temperature (Tg) or by the polymer's rigidity index. The glass transition temperature (Tg) can be estimated using the Fox equation or by differential calorimetry. The polymer's rigidity index can also be expressed as the polymer's mean square end-to-end distance, which can be measured by light scattering. Specifically, the functional structural unit is one or more combinations of N-isopropylacrylamide, N-hydroxymethylacrylamide, glycidyl methacrylate, and β-acryloyloxypropionic acid.

[0018] In addition, the present invention can also use other functional monomers. The aforementioned construction through some late-stage polymer modification methods refers to the addition of reactive functional groups to the polymer chain side.

[0019] In the above-mentioned polymer, the weight ratio of the acrylamide structural unit, cationic structural unit, and functional structural unit is 70-95:1-30:1-10. Preferably, the weight ratio of the acrylamide structural unit, cationic structural unit, and functional structural unit is 77-84:10-14:5-9; more preferably, the weight ratio of the acrylamide structural unit, cationic structural unit, and functional structural unit is 77.6-83.8:10.4-13.8:5.6-8.4.

[0020] Meanwhile, the present invention also discloses a method for preparing a polymer for paper strengthening agent as described above, characterized in that it is prepared by free radical solution polymerization. Specifically, the method involves dispersing acrylamide structural units, cationic structural units, functional structural units, and a structure regulator in water, and carrying out a polymerization reaction under the action of an initiator; the structure regulator is used to adjust the molecular weight and / or molecular weight distribution of the polymer.

[0021] The structure modifier is a chemical substance that imparts a specific structure to the polymer. Here, "structure" refers to a polymer with a low molecular weight distribution coefficient, typically formed through a chain reaction process involving chain radical growth. This chain reaction process involves controlling the transformation and linking of active and inactive polymer chains during the polymerization chain growth stage. Preferably, this is achieved by deactivating one or more active polymer chains to form a final product with a specific structure. Preferably, the structure modifier is one or more combinations of sodium hypophosphite, organic acids, and thiols; the structure modifier is equivalent to 0.01–0.2 wt% of the total monomer weight; the amount of water is equivalent to 4–5 times the total monomer weight; the initiator is a water-soluble initiator; and the initiator is equivalent to 0.1–0.3 wt% of the total monomer weight. The water-soluble initiator is a water-soluble redox initiation system, which includes a water-soluble oxidant and a water-soluble reductant; the water-soluble oxidant includes persulfate, hydrogen peroxide, bromate, etc., and the water-soluble reductant includes sulfite, metabisulfite, thiosulfate, etc.; the water-soluble initiator also includes a water-soluble thermal initiator, which includes, but is not limited to, water-soluble azo compounds; the water-soluble azo compounds include at least 2,2'-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride, azobisisobutylamidine hydrochloride, etc.

[0022] In the above preparation method, the reaction temperature of the free radical solution polymerization is 30-95℃, and the reaction time is 2-6h; the initiator is added to the reaction system dropwise; preferably, the reaction temperature of the free radical solution polymerization is 65℃-90℃, and the reaction time is 3-5h.

[0023] Finally, the present invention also discloses a paper strengthening agent, obtained by reacting a polymer and an aldehyde agent as described above. Preferably, the mass ratio of the polymer to the aldehyde agent is 3:1 to 14:1; more preferably 4:1 to 8:1, particularly preferably 4.4:1 to 7:1; the pH value of the reaction system is 8 to 12; more preferably 9.5 to 10.5; the weight-average molecular weight of the paper strengthening agent is 500,000 to 5,000,000, and the distribution coefficient is 3 to 8; preferably, the weight-average molecular weight of the paper strengthening agent is 843,000 to 1,112,000, and the distribution coefficient is 5.1 to 5.7. The aldehyde agent is a compound containing two or more aldehyde groups, preferably a dialdehyde, particularly preferably glyoxal or glutaraldehyde.

[0024] The present invention has the following advantages and effects compared with the prior art:

[0025] (1) The reinforcing agent provided by the present invention is a composition with moderate molecular weight, smaller dispersion coefficient, higher network density and more rigid molecular chain.

[0026] (2) In paper wet-end chemistry, fine fibers are easily lost with white water, resulting in lower strength of the product due to less bonding. Simultaneously, the key to effective reinforcement lies in how quickly, stably, and effectively the polymer used as a reinforcing agent binds to the fibers. If the molecular weight is too large or too small, it cannot bind well to the fibers. Firstly, as water flows away, the fibers quickly bond together due to capillary action, allowing smaller polymer molecules to bind to the fibers more quickly. However, due to limited contact sites, larger polymer molecules are excluded, ultimately impairing the reinforcing effect. Conversely, if the polymer molecular weight is too large, it cannot act on the fiber interior before the capillary action disappears, and the bonding between fibers consists only of their respective hydrogen bonds, also impairing the reinforcing effect. Therefore, appropriate molecular weight and distribution are crucial factors for reinforcement. Finally, since the polymer is ultimately incorporated into the finished fiber, the strength of its interaction with the fiber, i.e., the bond energy, is important, as is the strength of the polymer itself.

[0027] When the reinforcing agent provided by this invention is added to the middle of the fiber, the special polymer network structure of this invention can provide excellent ability to retain fine fibers, thereby retaining more fibers and forming more fiber bonds. Compared with the blank, the retention of the product of this invention reaches more than 30%.

[0028] Meanwhile, the molecular weight and distribution of the present invention are more suitable, ranging from 800,000 to 1,600,000, with a distribution coefficient between 4 and 6. Finally, some reaction sites of the product further form a relatively strong covalent bond system with the fiber or itself after the paper drying process, and the strength of the resulting product is greatly improved. Detailed Implementation

[0029] The present invention will now be clearly and completely described in conjunction with embodiments thereof. It should be noted that, unless specific conditions are specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.

[0030] Example 1

[0031] Prepare according to the following proportions (parts by weight):

[0032] 3000 parts of acrylamide;

[0033] 1200 parts of methacrylamide;

[0034] 290 parts of N-hydroxymethylacrylamide;

[0035] 720 parts of diallyl dimethyl ammonium chloride;

[0036] 8 parts sodium hypophosphite

[0037] 4.3 parts of ammonium persulfate;

[0038] Sodium metabisulfite 1.8 parts;

[0039] Adjust the water content to approximately 17.5% for effective fraction.

[0040] Weigh out all components except ammonium persulfate and sodium metabisulfite, mix them, and then purge with nitrogen to remove oxygen for half an hour. Add ammonium persulfate and sodium metabisulfite dropwise at 60°C while reacting for 3 hours. Keep warm for 1 hour to obtain the first polymer.

[0041] Take 200 parts by weight of the effective solid content of the polymer from the first polymerization, add 50 parts by weight of glyoxal and mix. React at pH 10 and temperature 30°C for 20 minutes to obtain composition 1.

[0042] Example 2

[0043] Prepare according to the following proportions (parts by weight):

[0044] 3000 parts of acrylamide;

[0045] 1200 parts of methacrylamide;

[0046] 450 parts of glycidyl methacrylate;

[0047] 720 parts of diallyl dimethyl ammonium chloride;

[0048] 8 parts sodium hypophosphite

[0049] 4.3 parts of ammonium persulfate;

[0050] Sodium metabisulfite 1.8 parts;

[0051] Adjust the water content to approximately 17.5% for effective fraction.

[0052] Weigh out all components except ammonium persulfate and sodium metabisulfite, mix them, and then purge with nitrogen to remove oxygen for half an hour. Add ammonium persulfate and sodium metabisulfite dropwise at 60°C while reacting for 3 hours. Keep warm for 1 hour to obtain the first polymer.

[0053] Take 200 parts by weight of the effective solid content of the polymer from the first polymerization, add 50 parts by weight of glyoxal and mix. React at pH 10 and temperature 30°C for 20 minutes to obtain composition 2.

[0054] Example 3

[0055] Prepare according to the following proportions (parts by weight):

[0056] 3000 parts of acrylamide;

[0057] 1200 parts of methacrylamide;

[0058] 150 parts of N-hydroxymethylacrylamide

[0059] 220 parts of glycidyl methacrylate;

[0060] 720 parts of diallyl dimethyl ammonium chloride;

[0061] 8 parts sodium hypophosphite

[0062] 4.3 parts of ammonium persulfate;

[0063] Sodium metabisulfite 1.8 parts;

[0064] Adjust the water content to approximately 17.5% for effective fraction.

[0065] Weigh out all components except ammonium persulfate and sodium metabisulfite, mix them, and then purge with nitrogen to remove oxygen for half an hour. Add ammonium persulfate and sodium metabisulfite dropwise at 60°C while reacting for 3 hours. Keep warm for 1 hour to obtain the first polymer.

[0066] Take 200 parts by weight of the effective solid content of the polymer from the first polymerization, add 50 parts by weight of glyoxal and mix. React at pH 10 and temperature 30°C for 30 minutes to obtain composition 3.

[0067] Example 4

[0068] Prepare according to the following proportions (parts by weight):

[0069] 3000 parts of acrylamide;

[0070] 1200 parts of methacrylamide;

[0071] 450 parts of β-carboxyethyl acrylate;

[0072] 720 parts of diallyl dimethyl ammonium chloride;

[0073] 8 parts sodium hypophosphite

[0074] 4.3 parts of ammonium persulfate;

[0075] Sodium metabisulfite 1.8 parts;

[0076] Adjust the water content to approximately 17.5% for effective fraction.

[0077] Weigh out all components except ammonium persulfate and sodium metabisulfite, mix them, and then purge with nitrogen to remove oxygen for half an hour. Add ammonium persulfate and sodium metabisulfite dropwise at 60°C while reacting for 3 hours. Keep warm for 1 hour to obtain the first polymer.

[0078] Take 200 parts by weight of the effective solid content of the polymer from the first polymerization, add 50 parts by weight of glyoxal and mix. React at pH 10 and temperature 30°C for 20 minutes to obtain composition 4.

[0079] Example 5

[0080] Prepare according to the following proportions (parts by weight):

[0081] 2000 parts of acrylamide;

[0082] 2200 parts of methacrylamide;

[0083] 290 parts of N-hydroxymethylacrylamide;

[0084] 520 parts of diallyl dimethyl ammonium chloride;

[0085] 8 parts sodium hypophosphite

[0086] 4.3 parts of ammonium persulfate;

[0087] Sodium metabisulfite 1.8 parts;

[0088] Adjust the water content to approximately 17.5% for effective fraction.

[0089] Weigh out all components except ammonium persulfate and sodium metabisulfite, mix them, and purge with nitrogen for half an hour to remove oxygen. Add ammonium persulfate and sodium metabisulfite dropwise at 60°C while reacting for 3 hours. Keep warm for 1 hour to obtain the first polymer.

[0090] Take 200 parts by weight of the effective solid content of the polymer from the first polymerization, add 50 parts by weight of glyoxal and mix. React at pH 10 and temperature 30°C for 20 minutes to obtain composition 5.

[0091] Example 6

[0092] Prepare according to the following proportions (parts by weight):

[0093] 3500 parts of acrylamide;

[0094] 700 parts of methacrylamide;

[0095] 290 parts of N-hydroxymethylacrylamide;

[0096] 920 parts of diallyl dimethyl ammonium chloride;

[0097] 8 parts of 2-propanethiol

[0098] 4.3 parts of ammonium persulfate;

[0099] Sodium metabisulfite 1.8 parts;

[0100] Adjust the water content to approximately 17.5% for effective fraction.

[0101] Weigh out all components except ammonium persulfate and sodium metabisulfite, mix them, and purge with nitrogen for half an hour to remove oxygen. Add ammonium persulfate and sodium metabisulfite dropwise at 60°C while reacting for 3 hours. Keep warm for 1 hour to obtain the first polymer.

[0102] Take 200 parts by weight of the effective solid content of the polymer from the first polymerization, add 50 parts by weight of glyoxal and mix. React at pH 10 and temperature 30°C for 20 minutes to obtain composition 6.

[0103] Comparative Example 1

[0104] Prepare according to the following proportions (parts by weight):

[0105] 3200 parts of acrylamide;

[0106] 1200 parts of methacrylamide;

[0107] 720 parts of diallyl dimethyl ammonium chloride;

[0108] 8 parts sodium hypophosphite

[0109] 4.3 parts of ammonium persulfate;

[0110] Sodium metabisulfite 1.8 parts;

[0111] Adjust the water content to approximately 17.5% for effective fraction.

[0112] Weigh out all components except ammonium persulfate and sodium metabisulfite, mix them, and purge with nitrogen for half an hour to remove oxygen. Add ammonium persulfate and sodium metabisulfite dropwise at 60°C while reacting for 3 hours. Keep warm for 1 hour to obtain the first polymer.

[0113] Take 200 parts by weight of the effective solid content of the polymer from the first polymerization, add 50 parts by weight of glyoxal and mix. React at pH 10 and temperature 30°C for 20 minutes to obtain composition 7.

[0114] Comparative Example 2

[0115] Prepare according to the following proportions (parts by weight):

[0116] 3200 parts of acrylamide;

[0117] 1200 parts of methacrylamide;

[0118] 720 parts of diallyl dimethyl ammonium chloride;

[0119] Ammonium persulfate 6.3 parts;

[0120] Sodium metabisulfite 2.6 parts;

[0121] Adjust the water content to approximately 17.5% for effective fraction.

[0122] Weigh out all components except ammonium persulfate and sodium metabisulfite, mix them, and purge with nitrogen for half an hour to remove oxygen. Add ammonium persulfate and sodium metabisulfite dropwise at 60°C while reacting for 3 hours. Keep warm for 1 hour to obtain the first polymer.

[0123] Take 200 parts by weight of the effective solid content of the polymer from the first polymerization, add 50 parts by weight of glyoxal and mix. React at pH 10 and temperature 30°C for 20 minutes to obtain composition 8.

[0124] Comparative Example 3

[0125] Prepare according to the following proportions (parts by weight):

[0126] 4400 parts of acrylamide;

[0127] 290 parts of N-hydroxymethylacrylamide;

[0128] 720 parts of diallyl dimethyl ammonium chloride;

[0129] 8 parts sodium hypophosphite

[0130] 4.3 parts of ammonium persulfate;

[0131] Sodium metabisulfite 1.8 parts;

[0132] Adjust the water content to approximately 17.5% for effective fraction.

[0133] Weigh out all components except ammonium persulfate and sodium metabisulfite, mix them, and purge with nitrogen for half an hour to remove oxygen. Add ammonium persulfate and sodium metabisulfite dropwise at 60°C while reacting for 3 hours. Keep warm for 1 hour to obtain the first polymer.

[0134] Take 200 parts by weight of the effective solid content of the polymer from the first polymerization, add 50 parts by weight of glyoxal and mix. React at pH 10 and temperature 30°C for 20 minutes to obtain composition 9.

[0135] The performance and formulation data of all compositions are shown in Table 1.

[0136] Table 1 Formulation and Performance Table

[0137]

[0138]

[0139]

[0140] The solid content determination method described in the table above refers to GB / T 12005.2-1989 "Method for Determination of Solid Content in Polyacrylamide";

[0141] The viscosity was measured using a Borlefeld rotational viscometer, rotor 1 at 60 PRM speed.

[0142] The molecular weight and distribution were measured using dynamic light scattering.

[0143] To evaluate the effect of the composition obtained in the examples, the obtained composition was added to the paper formulation as a reinforcing agent.

[0144] The paper formulation can have various compositions, which are distinguished here according to the ratio of broadleaf fiber and softleaf fiber. In order to distinguish the composition from the commercially available product (2% solid content, molecular weight of 580kD, distribution coefficient of 7.4, blue transparent aqueous solution) under different softleaf fiber reinforcement, the following scheme is selected as shown in Table 2.

[0145] Compositions 1-9 were added to pulp AC respectively, and the retention rate of short fibers (%), tensile index and bursting index of the finished paper were tested respectively. The results in Table 2 compare the performance of the compositions of the present invention and commercially available products.

[0146] Table 2. Pulp Information for Different Softwood Content

[0147]

[0148]

[0149] The specific operation is as follows: According to the pulp A / B / C ratio in Table 2, select softwood and hardwood pulps to mix, add water at a certain concentration to prepare a 10% fiber pulp, and use a Guangdong Internesson Instruments Co., Ltd. MJ01-RFI type refiner for 5000 revolutions; after refinement, further dilute the pulp concentration to 1%, and use a Changchun Mingyue Small Testing Machine Co., Ltd. CBJ-A type fiber standard dissociator for 15000 revolutions; then add 0.12% of the absolute solids content as reinforcement, and refine for another 5000 revolutions; use a PTA Group RK-2A type sheet-making machine to fry the sheets, accurately weighing each sheet at 80g ± 1g, and test the strength; simultaneously, place the 1% concentration frying pulp in a Mütek... TM .

[0150] Retention tests were conducted using the DFR-05 dynamic retention filtration instrument. Using unreinforced pulp as a blank sample, the performance increases of the reinforced sample compared to the blank sample are listed in Table 3 below.

[0151] The finished paper sheets were cut to a certain size. The tensile strength was tested using a WZL-C type horizontal computer tensile tester from China Building Materials Intelligent Automation Research Institute Co., Ltd.; the bursting strength was tested using a PN-BSM160F type paper bursting strength tester from Hangzhou Pinxiang Technology Co., Ltd.

[0152] The list shows the performance index improvement rate, which is defined as the performance increase rate divided by the paper weight; where the performance increase rate is the performance increase divided by the performance baseline of the blank sample. The specific formula is as follows:

[0153] Performance index growth rate % = (T1 - T0) / (T0 * W)

[0154] T1: Performance after adding reinforcing agents;

[0155] T0: Performance of the blank sample;

[0156] W: Paper weight

[0157] Table 3 Properties of different compositions

[0158]

[0159]

[0160] Results analysis:

[0161] As can be seen from compositions 1 to 6, the retention rate, tensile index increase rate, and bursting index increase rate of different papers are significantly better than those of compositions 7 to 9 and commercially available products. Furthermore, as the pulp changes from A to C, it is found that the tensile and bursting index increase rates of composition 3 are still over 20%, while the performance of compositions 7 to 9 and commercially available products decreases significantly with the increase of short fibers, thus limiting their application range.

[0162] As can be seen from the data in Table 1, the changes in the aforementioned properties are related to the polymer properties. For example, compositions 2 and 7 have very similar indices related to paper reinforcing agents, such as molecular weight and molecular weight distribution, but their properties differ significantly. This indicates that product performance is not solely determined by the molecular weight and molecular weight distribution of the paper reinforcing agent, but rather by the properties of the polymer. For instance, the polymers involved in compositions 2 and 7 do not use functional structural units. Furthermore, the polymers involved in composition 2 and composition 8 are relatively close in molecular weight, but the polymer involved in composition 8 not only does not use functional structural units, but its molecular weight distribution is also too large. This further illustrates that the functional structural units and molecular weight distribution of the polymer have a direct impact on product performance.

[0163] Therefore, we can draw a relatively clear conclusion that the possible factors causing the above-mentioned effects are: 1. the introduction of functional structural units; 2. the ingenious control of molecular weight and molecular weight distribution; in order to achieve affinity for fibers, especially short fibers, the hydrogen bonds, chemical bonds and physical entanglement between the polymer network and the fibers are used to improve fiber bonding and strength; in addition, as can be seen from the polymer of composition 9, the combined use of amide monomers is a powerful guarantee for improving performance.

Claims

1. A paper strengthening agent, characterized in that, It is obtained by reacting a polymer with an aldehyde agent; The polymer contains acrylamide structural units, cationic structural units containing cationic groups, and functional structural units for improving polymer rigidity or crosslinking density; the weight ratio of the acrylamide structural units, cationic structural units, and functional structural units is 77.6–83.8: 10.4–13.8: 5.6–8.4; the polymer has a weight-average molecular weight of 140,000–280,000 and a dispersion index of 2.3–2.

8. The mass ratio of the polymer to the aldehyde agent is 4:1 to 7:1; the pH value of the reaction system is 9.5 to 10.5; the aldehyde agent is a compound containing two or more aldehyde groups; the weight-average molecular weight of the paper strengthening agent is 843,000 to 1,112,000, and the distribution coefficient is 5.1 to 5.

7. The acrylamide structural unit is acrylamide or methacrylamide; the cationic structural unit is dimethyl diallyl ammonium chloride; and the functional structural unit is one or more combinations of N-isopropylacrylamide, N-hydroxymethylacrylamide, glycidyl methacrylate, and β-acryloyloxypropionic acid.

2. The paper strengthening agent according to claim 1, characterized in that, The polymer is prepared by free radical solution polymerization or free radical suspension polymerization.

3. The paper strengthening agent according to claim 2, characterized in that: The method specifically involves dispersing acrylamide structural units, cationic structural units, functional structural units, and a structure regulator in water, and carrying out a polymerization reaction under the action of an initiator; the structure regulator is used to adjust the molecular weight and / or molecular weight distribution of the polymer.

4. The paper strengthening agent according to claim 3, characterized in that: The structure modifier is one or more combinations of sodium hypophosphite, organic acid, and thiol compound; the structure modifier is equivalent to 0.01~0.2 wt% of the total weight of the monomers; The amount of water used is equivalent to 4 to 5 times the total weight of the individual units; The initiator is a water-soluble initiator; the initiator is equivalent to 0.1 to 0.3 wt% of the total weight of the monomers.

5. The paper strengthening agent according to claim 3, characterized in that: The free radical solution polymerization reaction temperature is 30–95°C, and the reaction time is 2–6 h; the initiator is added to the reaction system dropwise.

6. The paper strengthening agent according to claim 5, characterized in that: The free radical solution polymerization reaction temperature is 65℃-90℃, and the reaction time is 3-5h.

7. The paper strengthening agent according to claim 1, characterized in that, The aldehyde oxidizing agent is glyoxal or glutaraldehyde.

Citation Information

Patent Citations

  • Composition and method for increasing wet and dry paper strength

    CN113785029A

  • Aqueous acetaldehyde acidified polyacrylamide composition

    CN116964147A

  • Papermaking reinforcing agent and preparation method thereof

    CN111732688A